(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The quality of residential areas and housing in various regions of Indonesia is experiencing a decline, both in urban and rural settings. However, issues regarding inadequate settlement areas still persist. Based on observations, apart from problems with the condition of housing structures, there are also challenges related to the availability of facilities and infrastructure. Incorrect utilization of these amenities is also a contributing factor to the decreasing housing quality in the settlement area of Lekobalo Village. So it is necessary to analyze the infrastructure planning of slum areas in Lekobalo Village.¬¬¬¬ This study aims to determine the infrastructure planning of the slum area and formulate an analysis of the calculation of the budget plan for the cost of handling the slum area of Lekobalo Village. This type of research is research that combines quantitative and qualitative. Data collection techniques, field observations and interviews. The results showed that residential buildings / houses have almost the same characteristics classified as poor, the condition of infrastructure and utility facilities, namely environmental road conditions, some locations are not served by environmental roads in accordance with technical provisions, drinking water supply conditions are not sufficient drinking water, drainage conditions of environmental drainage networks are unable to drain water runoff, wastewater management conditions do not have household wastewater management, and waste management conditions, the absence of waste collection facilities. The calculation of the cost budget plan, hot mix road planning, yields Rp. 3,380,002,558.71 (three billion three hundred eighty million two thousand five hundred and fifty-eight point seventy thousand seven hundred and fifty-one).The solution to handling slum areas is to improve the quality of the residential environment with restoration and resettlement focused on improving residential buildings, infrastructure and utility facilities.